2019
DOI: 10.1001/jama.2019.1347
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tramadol With All-Cause Mortality Among Patients With Osteoarthritis

Abstract: Surgeons guideline recommends tramadol for patients with knee osteoarthritis, and an American College of Rheumatology guideline conditionally recommends tramadol as first-line therapy for patients with knee osteoarthritis, along with nonsteroidal anti-inflammatory drugs.OBJECTIVE To examine the association of tramadol prescription with all-cause mortality among patients with osteoarthritis. DESIGN, SETTING, AND PARTICIPANTS Sequential, propensity score-matched cohort study at a general practice in the United K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
190
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(199 citation statements)
references
References 42 publications
4
190
1
4
Order By: Relevance
“…Increased mortality associated with prescriptions of opioids for chronic non‐cancer pain is one component of the North American opioid epidemic (Asbhurn & Fleisher, ). Prescription of tramadol for osteoarthritis pain in persons aged 50 years or more was associated with all‐cause mortality in an UK database of general practitioners between 2000 and 2015 (Zeng et al, ). In contrast, this systematic review found no increased mortality in the opioid group in the context of RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased mortality associated with prescriptions of opioids for chronic non‐cancer pain is one component of the North American opioid epidemic (Asbhurn & Fleisher, ). Prescription of tramadol for osteoarthritis pain in persons aged 50 years or more was associated with all‐cause mortality in an UK database of general practitioners between 2000 and 2015 (Zeng et al, ). In contrast, this systematic review found no increased mortality in the opioid group in the context of RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Tramadol, a commonly used weak opioid for the treatment of pain, has been considered an analgesic alternative, since its perceived risk of serious cardiovascular and gastrointestinal adverse effects was lower than that of nonsteroidal anti‐inflammatory drugs (NSAIDs), and its risk of addiction and respiratory depression was lower than that of traditional opioids . As a result, tramadol use has been increasing rapidly worldwide over the past decades .…”
Section: Introductionmentioning
confidence: 99%
“…Tramadol, a commonly used weak opioid for the treatment of pain, has been considered an analgesic alternative, since its perceived risk of serious cardiovascular and gastrointestinal adverse effects was lower than that of nonsteroidal anti‐inflammatory drugs (NSAIDs), and its risk of addiction and respiratory depression was lower than that of traditional opioids . As a result, tramadol use has been increasing rapidly worldwide over the past decades . For example, data from Truven Health Analytics MarketScan in the United States showed that prescriptions of tramadol increased by 22.8% between 2012 and 2015, and tramadol dispensing rates increased in each of the provinces in Canada, with the highest in Nova Scotia increasing from 0.50/defined daily doses (DDD) in 2007 to 2.64/DDD in 2016 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations